2003
DOI: 10.1021/ja037592g
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of an Electronically Switchable Rotaxane on the Surface of a Titanium Dioxide Nanoparticle

Abstract: This paper describes the self-assembly of a heterosupramolecular system consisting of a tripodal [2]rotaxane adsorbed at the surface of a titanium dioxide nanoparticle. The tripodal [2]rotaxane consists of a dumbbell-shaped molecule, incorporating two electron-poor viologens, threading an electron-rich crown ether. The [2]rotaxane also incorporates a bulky tripodal linker group at one end and a bulky stopper group at the other end. The [2]rotaxane is adsorbed, via the tripodal linker group, at the surface of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 22 publications
5
76
0
1
Order By: Relevance
“…Molecular machines (13)(14)(15)(16)(17) are attractive systems for deployment in the development of nanovalves on account of their abilities to be customized and optimized for a range of functions at the nanoscale. The attachment of supramolecular and molecular machines to nanoparticles has been achieved in a number (18)(19)(20)(21) of different classes of systems. In our most recent research, described in this report, the movable control element that has been used to control the flow of molecules in a nanovalve is a bistable, redox-controllable [2]rotaxane R 4ϩ , shown in Fig.…”
mentioning
confidence: 99%
“…Molecular machines (13)(14)(15)(16)(17) are attractive systems for deployment in the development of nanovalves on account of their abilities to be customized and optimized for a range of functions at the nanoscale. The attachment of supramolecular and molecular machines to nanoparticles has been achieved in a number (18)(19)(20)(21) of different classes of systems. In our most recent research, described in this report, the movable control element that has been used to control the flow of molecules in a nanovalve is a bistable, redox-controllable [2]rotaxane R 4ϩ , shown in Fig.…”
mentioning
confidence: 99%
“…4 The deposition of rotaxane molecules on solid surfaces 5,6 is a promising approach toward this purpose. Although the functionalization of the surface of solid materials, such as gold nanoparticles, 7 silica, 8 ITO electrodes, 9 and TiO 2 , 10 has been reported the effective introduction of interlocked molecules on the surface remains a challenge. In our previous research work, we reported synthesis of [2]rotaxanes composed of dibenzo [24]crown-8-ether and dialkylammonium with ferrocenyl and trisiloxysilyl or silsesquioxane terminal groups as well as their electrochemical properties.…”
Section: Rotaxanesmentioning
confidence: 99%
“…[19] The integration of such systems with surfaces in order to read out the logic operation remains, however, a scientific challenge. [20] A further interesting application includes the use of electrodriven molecular machines for the electrical contacting of redox enzymes. Redox enzymes lack direct electrical communication between their redox centers and electrode surfaces.…”
Section: Feature Articlementioning
confidence: 99%